Conceptualizing brand purpose and considering its implications for consumer eudaimonic well‐being - Williams, Patti; Escalas, Jennifer Edson; Morningstar, Andrew (Journal of Consumer Psychology, 2022)
AbstractIn response to high‐profile calls, and the apparent demand from consumers, brands in a wide variety of categories have sought to define, articulate, communicate, and act according to their “brand purpose.” But what is brand purpose? Human purpose is seen as a long‐term commitment to act consistently with one's values, leading to productive engagement with the world that transcends the self. However, the use of the term purpose as applied to brands raises a number of questions. In what ways is brand purpose similar to, and different from, human purpose? How do consumers react to brand purpose? How might a brand's purpose impact consumers? In this review, we explore the concept of brand purpose and its potential impact on consumer behavior, drawing upon the literature on human purpose. Additionally, we propose that engagement and connections with authentically purposeful brands may contribute to consumers' own purposeful lives, ultimately helping consumers achieve their own eudaimonic well‐being. We develop a framework highlighting the relationship between brand purpose and consumer eudaimonic well‐being to guide future research in this domain.